2020
DOI: 10.1149/1945-7111/abbe5b
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Failure in Li[Ni0.5Mn0.3Co0.2]O2/Graphite Pouch Cells Due to Low LiPF6 Concentration and Extended Time at High Voltage

Abstract: Li[Ni0.5Mn0.3Co0.2]O2/graphite pouch cells were cycled using protocols that included 24 h spent at high voltage (≥ 4.3 V) under constant voltage or open circuit conditions to accelerate failure. Compared to traditional cycling, failure was reached up to 3.5 times faster. When this protocol was applied to cells containing low LiPF6 concentrations (≤ 0.4 M) failure was achieved up to 17.5 times faster than traditional cycling with normal LiPF6 concentrations. This represents a time improvement on the order of ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…The most common electrolyte salt used in modern Li-ion cells containing a liquid electrolyte is lithium hexafluorophosphate, with concentrations ranging from 0.8 to 2 M with near-maximum conductivity. Its solutions in a binary or ternary mixture of cyclic carbonates, e.g., ethylene carbonate (EC) or propylene carbonate (PC) and linear carbonates, e.g., dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC), show high ionic conductivity, low viscosity, and good electrochemical stability . Despite the drawbacks of this salt, such as its thermal and chemical decomposition in the presence of traces of water (i.e., it releases hydrofluoric acid (HF), phosphoric acid (H 3 PO 4 ), and lithium fluoride (LiF)), it remains essential in practice due to its contribution to the formation of a solid electrolyte interface (SEI) layer at the anode (graphite) and its ability to passivate the aluminum current collector at the cathode.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The most common electrolyte salt used in modern Li-ion cells containing a liquid electrolyte is lithium hexafluorophosphate, with concentrations ranging from 0.8 to 2 M with near-maximum conductivity. Its solutions in a binary or ternary mixture of cyclic carbonates, e.g., ethylene carbonate (EC) or propylene carbonate (PC) and linear carbonates, e.g., dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC), show high ionic conductivity, low viscosity, and good electrochemical stability . Despite the drawbacks of this salt, such as its thermal and chemical decomposition in the presence of traces of water (i.e., it releases hydrofluoric acid (HF), phosphoric acid (H 3 PO 4 ), and lithium fluoride (LiF)), it remains essential in practice due to its contribution to the formation of a solid electrolyte interface (SEI) layer at the anode (graphite) and its ability to passivate the aluminum current collector at the cathode.…”
mentioning
confidence: 99%
“…High salt concentrations in LIBs exist mostly as ion pairs with low solvation number . These solutions protect the current collector against corrosion and provide a longer cycle life and improved safety. , Still, large salt concentrations lead to an amplified gas evolution, decreased ionic mobility and fluidity, and, most importantly, added cost and environmental concerns. …”
mentioning
confidence: 99%
“…Individual cells, depicted in Figure 2, show a comparatively strong and sudden drop in capacity (tests 4,11,18,20), which is paired with a sharp increase in the 10s resistance. This behavior, often referred to as nonlinear aging [9], can have many causes, like accelerated loss of cyclable lithium, electrolyte consumption, electrode dry-out, pore clogging, and plating, most of which are closely related [9,14,[24][25][26]. However, tests 4, 18 and 20 clearly show that cells tested with the same conditions do not exhibit the same nonlinear aging behavior reproducibly.…”
Section: Modellingmentioning
confidence: 99%
“…Other studies also observed accelerated degradation at extreme SOCs. 123,161,162 The impact of the voltage window on knee onset is typically attributed to resistance growth stemming from enhanced expansion and cracking of the positive electrode during intercalation, driving electrolyte oxidation. 6,14,162 For some positive electrodes, transition metal migration (often manganese or iron) may also be exacerbated by high voltages.…”
Section: Voltage Limitsmentioning
confidence: 99%
“…123,161,162 The impact of the voltage window on knee onset is typically attributed to resistance growth stemming from enhanced expansion and cracking of the positive electrode during intercalation, driving electrolyte oxidation. 6,14,162 For some positive electrodes, transition metal migration (often manganese or iron) may also be exacerbated by high voltages. 161,163,164 Rests Like discharging rate, the effect of rests during cycling on the knee occurrence is mixed (Figure 20c-d).…”
Section: Voltage Limitsmentioning
confidence: 99%